Comparison of outcomes between minimally invasive percutaneous bunnell suture and traditional open modified Kessler technique for acute closed achilles tendon rupture: A single-center cohort study - Zihang Zhao; Xiang Zhang; Xi Hou; Zihan Liu; Zhiyong Hou; Lianxin Song; Ruipeng Zhang (PLoS ONE, 2025)
Percutaneous Bunnell repair and open modified Kessler repair remain debated options for acute Achilles tendon rupture (AATR). We retrospectively compared a minimally invasive percutaneous Bunnell technique (Group A) with an open modified Kessler repair (Group B) within a standardized early functional rehabilitation (EFR) protocol at a single center. Fifty-five adults with closed AATR treated between January 2021 and December 2022 were analyzed (Group A, n = 25; Group B, n = 30). Between-group comparisons used Welch t tests for continuous variables and χ² or Fisher exact tests for categorical variables; American Orthopaedic Foot & Ankle Society (AOFAS) and Achilles Tendon Total Rupture Score (ATRS) were assessed at 12 and 24 weeks, with Holm adjustment applied within each scale. Compared with Group B, Group A had shorter operative time (56.6 ± 15.1 vs 68.2 ± 23.2 minutes; mean difference −11.6; 95% CI −22.05 to −1.15; P = 0.030), less intraoperative blood loss (28.4 ± 8.4 vs 74.7 ± 19.4 mL; −46.3; 95% CI −54.22 to −38.38; P < 0.001), and a shorter length of stay (4.8 ± 2.0 vs 6.6 ± 2.9 days; −1.8; 95% CI −3.13 to −0.47; P = 0.009). At 12 weeks, AOFAS favored Group A (+1.36; 95% CI + 0.19 to +2.53; P = 0.047) and ATRS also favored Group A (+1.73; 95% CI + 0.48 to +2.98; P = 0.008). At 24 weeks, AOFAS was not different (+0.51; 95% CI −0.49 to +1.51; P = 0.312), whereas ATRS remained higher in Group A (+2.17; 95% CI + 0.88 to +3.46; P = 0.003). Overall complications were 12.0% vs 26.7% (risk difference −14.7%; 95% CI −34.10 to +7.20; P = 0.310); no sural nerve injuries occurred. Within an EFR framework, percutaneous Bunnell repair provided superior perioperative efficiency with comparable safety and modest, sub-MCID functional advantages, supporting confirmation in larger prospective studies.